The Innovative Bureaucracy: Bureaucracy in an age of fluidity - Alexander Styhre (Alexander Styhre, 2007)
this book is the outcome of my own inability to really understand the problem with bureaucracy as such; isnâ€™t bureaucracy just one type of organizational arrangement whose content rather than form determines its outcome and effects? What struck me is that it is, in fact, the very form as such that seems to enrage both the proverbial â€œwo/man on the streetâ€ and the more theoretically inclined social scientist. Contemporary everyday speech is infested with a rich variety of derogatory remarks on bureaucracy and stories of how it fails to function or fails to provide meaningful work assignments abound. This veritable mythology of the shortcomings of bureaucracy is shared between folk psychology, popular culture and scholarly works. Moreover, what is confusing for us â€“ perhaps not too many, one may ask? â€“ having positive experiences of bureaucracy is that most dismissive remarks on the subject appear to be based on what is often referred to as â€œanecdotal evidenceâ€ by positivists; that is, idiosyncratic and contextualized experiences, or even by mere hearsay and common-sense thinking. Like in all mythologies, the deeply imbued belief that bureaucracy is a suspicious thing is a self-perpetuating axiom that one cannot easily falsify without deconstructing underlying and rarely articulated assumptions. Bureauphobia â€“ the systematic disbelief in bureaucracy â€“ is here fixed in the form that Pierre Bourdieu calls doxa. In order to defamiliarize what one already knows, empirical studies may hopefully play a role. This book is therefore an attempt at critically examining the literature on bureaucracy and the various organizational arrangements that have been jointly referred to as â€œpost-bureaucratic organizationâ€. In addition, the book presents two studies of large Swedish companies employing a bureaucratic form to organize their activities. Finally, a more affirmative image of bureaucracy than the conventional mechanistic metaphors is sketched in the final chapter. The aim of the book is thus to make bureaucracy a domain of empirical research anew, rather than serving as a â€œstraw manâ€ or a signifier denoting an antiquated organization form always already dismissed as being out of step with contemporary times. The other aim is to speak of bureaucracy in terms of change, movement and adaptation rather than stability, closure and even petrification. Therefore, notions such as vitalism, organism and becoming, derived from a bio-philosophical discourse, are brought into discussion in the sixth and final chapter.